Availability of Medications for the Treatment of Alcohol and Opioid Use Disorder in the USA - Abraham, Amanda J. (Neurotherapeutics, 2020)
Despite high mortality rates due to opioid overdose and excessive alcohol consumption, medications for the treatment of alcohol and opioid use disorder have not been widely used in the USA. This paper provides an overview of the literature on the availability of alcohol and opioid used disorder medications in the specialty substance use disorder treatment system, other treatment settings and systems, and among providers with a federal waiver to prescribe buprenorphine. We also present the most current data on the availability of alcohol and opioid use disorder medications in the USA. These estimates show steady growth in availability of opioid use disorder medications over the past decade and a decline in availability of alcohol use disorder medications. However, overall use of medications in the USA remains low. In 2017, only 16.3% of specialty treatment programs offered any single medication for alcohol use disorder treatment and 35.5% offered any single medication for opioid use disorder treatment. Availability of buprenorphine-waivered providers has increased significantly since 2002. However, geographic disparities in access to buprenorphine remain. Some of the most promising strategies to increase availability of alcohol and opioid use disorder medications include the following: incorporating substance use disorder training in healthcare education programs, educating the substance use disorder workforce about the benefits of medication treatment, reducing stigma surrounding the use of medications, implementing medications in primary care settings, implementing integrated care models, revising regulations on methadone and buprenorphine, improving health insurance coverage of medications, and developing novel medications for the treatment of substance use disorder.